AN EFFECTIVE WAY TO DETECT COMPUTER NETWORK ANOMALIES - Sa’dullayev , Avaz Akmal o‘g‘li (Educational Research in Universal Sciences, 2023)
With increased threat on the network, the detection of network anomalies is becoming more complicated. This thesis looked at anomaly detection by modeling a computer network as a temporary network.